Contraceptive use Among Hispanic Women Living in Puerto Rico - De León-Arbucias, Jeidiel; Acevedo-Canabal, Jorge; Marin-Alvarez, Jeyka; Benabe, Erika; Romaguera, Josefina (Puerto Rico Health Sciences Journal, 2023)
Objective: To assess the contraceptive methods used by sexually active Hispanic women living in Puerto Rico. Methods: From October 2016 through February 2018, 518 patients completed a self-administered questionnaire. The inclusion criteria were being over the age of 21 and having visited San Juan City Hospital or University District Hospital. The results were analyzed using descriptive statistics and a 2-sample t test, where P < .05 was considered significant. Results: A total of 518 participants completed the questionnaire. Of the 518, 413 (81.0%) reported having used at least 1 form of contraception; 252 (49.4%) used OCPs, 305 (60.8%) used male condoms, 92 (33.8%) used the rhythm method, 83 (30.6%) undergone female sterilization, 98 (19.9%) used the withdrawal method, 92 (18.9%%) used an implant, 67 (13.5%) received progesterone injections, 41 (8.3%) used female condoms, 13 (4.9%) had partners who undergone male sterilization, 20 (4.1%) used the transdermal patch, 16 (3.2%) used a vaginal ring, and 26 (5.3%) used an intrauterine device. Conclusion: Of the 518 women, 24.2% used LARC, representing an increase in the usage by this population; this increase is likely linked to LARC’s being easily accessible and free of charge. Public health interventions should be developed to increase knowledge about sexual health, educate about the effectiveness of different contraceptive methods and the prevention of sexually transmitted diseases, and reduce both the barriers to acquiring contraception and, thereby, the number of unintended pregnancies in this population.